Investigating the impact of HVAC and Sanitizer system design on the transmission of SARS-CoV-2 in Hospital Isolation Units - Amahjour, Narjisse; Sofi, Anas; Kamal, Tariq; El Kharrim, Abderrahman (Elsevier, 2024)
The COVID-19 pandemic has presented unprecedented challenges to healthcare facilities worldwide. Hospital isolation units have played a crucial role in the management of COVID-19 patients. However, the transmission of the virus within these units can lead to severe consequences for patients, healthcare workers, and the broader community. This research proposes a framework to evaluate the impact of HVAC (Heating, Ventilation, and Air Conditioning) and sanitizer system design on the transmission of SARS-CoV-2 in isolation unit at Saniat Rmel Hospital in Tetouan Morocco by using computational fluid dynamics (CFD) and the realizable turbulence model. Furthermore, the study investigates the effect of different inlet air velocities on the dispersion of airborne viral particles in the isolation unit. The results indicate that the air change rate plays a critical role in the spread and concentration of pathogens in the isolation unit. It was determined that the high inlet air velocity can lead the particles fluid including the virus reaches the exhaust port in a short time, in addition, it can facilitate the distribution of sanitizer throughout an isolation unit, which could potentially reduce the concentration of the virus. The outcome suggests that the placement and orientation of the air conditioner combined with the sanitizer system have a significant impact on the movement characteristics of fluid particles within the enclosed environment.
Keywords: Virus; Isolation room; HVAC; Sanitizer machine; Air velocity; computational fluid dynamics; fi=Sähkötekniikka|en=Electrical Engineering|